Transforming teacher education through service-learning - Jagla, Virginia M.; Tinkler, Alan S.; Erickson, Joseph A. (Advances in service-learning research., 2013)
Transforming Teacher Education through Service-Learning provides a fresh look at educational reform through the lens of teacher preparation. It poses the question "Why service-learning now?" as it discusses the meaningful ways service-learning pedagogy can transform the approaches used to prepare teachers to educate tomorrow's children.The pedagogy of service-learning has significant implications for teacher education. Its transformative aspects have far reaching potential to address teacher candidate dispositions and provide deeper understanding of diversity. Knowledge of the pedagogy and how to implement it in candidates' future classrooms could alter education to a more powerful experience of democracy in action and enhance the civic mission of schools. The current and ongoing research found within this volume is meant to continue support of the notion of educational reform.Because the vision we hold becomes the reality we experience, it is imperative to consider the question--Why service-learning now?--as we adjust teacher preparation programs to promote engaging opportunities for today's youth.